Changes in the Structure of Nest Complexes of the Red Wood Ants Formica rufa and F. polyctena (Hymenoptera, Formicidae) in Urban Forests - Stukalyuk, S.; Goncharenko, I.; Kozyr, M. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
The aim of this work is to evaluate changes in the structure of nest complexes of two species of red wood ants: Formica rufa Linnaeus, 1761 and F. polyctena Foerster, 1850, in the city of Kyiv (Ukraine) using morpho[1]metric indicators, as well as to evaluate their dynamics. In 2014–2022, nest complexes of two species of red wood ants (Formica rufa, F. polyctena) were observed in urbanised forests within the city of Kyiv. A total of 472 F. rufa and 411 F. polyctena nests were studied in 7 nest complexes (4 — F. polyctena, 3 — F. rufa). The total volume of F. polyctena nests were found to decrease by 2020–2021, while the volume of F. rufa nests remained at the same level or even increased. This suggests that F. rufa is more resistant to changes in forestry conditions.